THE INFLUENCE OF SIZE EFFECT ON THE FRACTURE STRENGTH OF UNIDIRECTIONAL GLASS FIBER REINFORCED POLYPROPYLENE COMPOSITE - ZHU YuYang; ZHAI JianGuang; GAO Chun; LU HuiQin (Jixie qiangdu)
In order to explore the influence of the size effect on the fracture strength of unidirectional continuous glass fiber reinforced polypropylene composites（unidirectional GF/PP composites）, the Zwick/Roell Z005 universal material testing machine was used to test different gauge lengths through orthogonal test methods.（60 mm, 100 mm, 200 mm）, unidirectional GF/PP composites with different widths（10 mm, 15 mm, 20 mm） are subjected to tensile test. The test results show that as the test size increases, the breaking strength of unidirectional GF/PP composites gradually decreases. Because the fracture strength of unidirectional GF/PP composites has a large dispersion, the distribution law of the strength of unidirectional GF/PP composites under different size conditions is obtained through the classic two-parameter Weibull strength statistical model, and the improved generalized The two-parameter weakest chain strength statistical model introduces the exponential parameterβto modify the influence of the spatial distribution of defects. The fracture strength data under different sizes are processed in a unified manner. The resulting failure function comprehensively reflects the size effect on the unidirectional GF/PP composite The effect of material breaking strength.